Die wit kerk en swart nood: Is daar nog sout in die soutpot oor? Opmerkings oor die betrokkenheid van die wit kerk by die MIV/Vigs pandemie in Suid-Afrika - Schoeman, L. G. (Verbum et ecclesia, 2002)
The white church and black needs: Is there still salt left in the salt cellar? Remarks on the involvement of the white church with the HIV/Aids pandemic in South Africa. There are reasons why the churches in the white community of South Africa are not really concerned or involved in the HIV/Aids pandemic, which is primarily ravaging the Black community. This may, however, be regarded as the "shibolet" for the credibility of the church. The article emphasises the need for the (White) church to listen in three directions: to understand its own identity, to listen (again) to the will of the Lord, and to listen to the needs of the Black community (especially in terms of HIV/Aids). Then the church should become involved. This involvement must be above else in the local communities, in the practical ways, which are indicated, in the area of short-term help, but also empowerment and liberation.